2019
DOI: 10.1080/24694452.2019.1593817
|View full text |Cite
|
Sign up to set email alerts
|

Networks of (Dis)connection: Mobility Practices, Tertiary Streets, and Sectarian Divisions in North Belfast

Abstract: Long-standing tensions between Protestant and Catholic communities in Northern Ireland have led to high levels of segregation. This article explores the spaces within which residents of north Belfast move within everyday life and the extent to which these are influenced by segregation. We focus in particular on the role that interconnecting tertiary streets have on patterns of mobility. We adapt Grannis's (1998) concept to define T-communities from sets of interconnecting tertiary streets within north Belfast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…Abundant emerging studies have uncovered new insights into individual human activity patterns in the urban environment, using various types of data sources and methods. For example, GPS (Global Positioning System) tracks of residents were used to study daily mobility patterns between two local communities (Davies et al 2019), longitudinal survey data were used to explore the community structures in people's collective activity space (Xi, Calder, and Browning 2020). González, Hidalgo, and Barabási (2008), using mobile phone call data in the form of call detail records (CDR), revealed that trajectories of human movements across the urban space are not random but show a high degree of spatial and temporal regularity.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Abundant emerging studies have uncovered new insights into individual human activity patterns in the urban environment, using various types of data sources and methods. For example, GPS (Global Positioning System) tracks of residents were used to study daily mobility patterns between two local communities (Davies et al 2019), longitudinal survey data were used to explore the community structures in people's collective activity space (Xi, Calder, and Browning 2020). González, Hidalgo, and Barabási (2008), using mobile phone call data in the form of call detail records (CDR), revealed that trajectories of human movements across the urban space are not random but show a high degree of spatial and temporal regularity.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Location‐based data, including global positioning system (GPS) devices and geographic information systems (GIS) data, have proven useful in examining PA in other populations. 51 , 52 , 53 However, the assessment of children's activity places using location‐based data is limited among Latino youth. 54 , 55 The use of such technologies to explore multilevel influences of PA will provide a better understanding of mobility patterns and activity places in Latino and Latin American youth.…”
Section: Resultsmentioning
confidence: 99%
“…Innovative strategies that examine behavioral patterns and routes of children's daily activities may help in understanding and in the identification of their activity places. Location‐based data, including global positioning system (GPS) devices and geographic information systems (GIS) data, have proven useful in examining PA in other populations 51–53 . However, the assessment of children's activity places using location‐based data is limited among Latino youth 54,55 .…”
Section: Resultsmentioning
confidence: 99%
“…The Belfast Mobility Project (BMP) has explored the nature, causes, and consequences of sectarian segregation in the historically divided city of Belfast, Northern Ireland's capital city. Whereas most research on this topic has focused on residential demography, mainly using government census data, the BMP investigated how segregation can arise through everyday mobility practices in activity spaces beyond the home (e.g., see Davies et al, 2019;Dixon et al, 2020Dixon et al, , 2022Hocking et al, 2018;Huck et al, 2019). To do so, we have gathered data using a range of methods, two of which we consider here.…”
Section: The Belfast Mobility Projectmentioning
confidence: 99%